Self-Predicted Future Usage of Malaysian Schools Student Information System - Mohamad Ishak, Mohamad (2005)
This report discusses a study that deals with the assessment of users’ subjective perception of the Malaysian School Student Information System (MSSIS). Currently, MSSIS is utilized for the collection of data from primary schools throughout the nation and a form of assessment is needed before expanding the system to include secondary schools which will eventually involve more than 9,000 schools under the Education Ministry. Theories of information technology acceptance are discussed and three models of in formation technology acceptance (Theory of Reasoned Action, Innovation Diffusion Theory, and Technology Acceptance Model) are compared. Based on these discussions, a research model is proposed to measure the acceptance level of the current MSSIS users. Questionnaires aimed at the assessment of users’ perceived usefulness and ease of use of information technology, were utilized. Pilot test involving 55 trainee teachers reveals that both usefulness and ease of use scales are highly reliable (Cronbach’s Alpha > 0.8). A survey was conducted with a sample of 92 users (primary school teachers) in the state of Perak. The analysis carried out to predict the future usage of MSSIS shows that the systern is accepted by its users and by accepting MSSIS; they are willing to use it in future. Test result also shows that gender, age group, and computer experience had no significant influence on users’ perceived usefulness, perceived ease of use and self-predicted future usage of MSSIS. Correlation results show that both perceived usefulness and ease of use constructs directly influence future usage of MSSW. Thus, it is possible to assume that MSSIS can be successfully expanded to secondary school.